Analytical Separation Science 2015
DOI: 10.1002/9783527678129.assep044
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Thin‐Layer Chromatography

Abstract: The instrumental modularity of its basic steps, that is, sample application, chromatographic development, and detection, confers HPTLC a high degree of flexibility. Automated and computer‐controlled instruments with different levels of sophistication for each of these steps have been developed, for example, spray‐on sample applicators and chambers including the possibility of gradient separation. Detection techniques such as scanning densitometers, electronic documentation systems, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…Squalene, however, has a polarity that is relatively close to squalane, which makes their separation difficult (e.g., no narrow signals) under the studied conditions (Figure 1). The resolving power of PMC may also be affected by matrix effects, evidenced by signal‐broadening of phytol and squalene when chromatographed as a sample mixture, a phenomenon known in TLC and other chromatographic approaches [2]. Increasing of the migration distance (over 40 mm) can potentially improve the separation, however, it also increases the diffusion of the analyte on the membrane, affecting the signal resolution (Figure S3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Squalene, however, has a polarity that is relatively close to squalane, which makes their separation difficult (e.g., no narrow signals) under the studied conditions (Figure 1). The resolving power of PMC may also be affected by matrix effects, evidenced by signal‐broadening of phytol and squalene when chromatographed as a sample mixture, a phenomenon known in TLC and other chromatographic approaches [2]. Increasing of the migration distance (over 40 mm) can potentially improve the separation, however, it also increases the diffusion of the analyte on the membrane, affecting the signal resolution (Figure S3).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we showed that PVDF membranes can also be used as the stationary phase in planar chromatographic assays of lipids and hydrocarbons of diverse origin, an application that, to our knowledge, has not been yet reported. Consequently, similar TLC applications and advantages are shared by PMC, such as the possibility of studying all nonvolatile analytes in a sample, applying different detection techniques and effect‐directed analysis to the same chromatographic run, reduced cost, high sample throughput, and overall simplicity compared to column chromatographic methods [2,4]. We showed that is possible to separate hydrocarbons and lipids from complex samples by PMC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of an elution-based interface to directly coupling HPTLC with ESI-MS equipments has become popular and has been applied to a wide number of analytes, including lipids [2,3]. Using this interface, a modular, simple, rapid and direct transfer of separated HPTLC bands can be achieved in the desired zones of the plate, owing to: the open HPTLC configuration; the post-chromatographic removal of the mobile phase before extraction by the interface solvent; and the previous detection of the relevant chromatographic zones by densitometry.…”
Section: Introductionmentioning
confidence: 99%